SYNTHESIS OF CARBON NANOSTRUCTURES UNDER INTENSIVE CAVIATION - Dorokhov, Victor; Hauser, Yulia (Revista Inclusiones, 2020)
For aqueous disperse systems colloidal stabilization of the organic copper phthalocyanine pigment (CuPc), there were used series of homo- and block copolymers of methyl vinyl (MVE) and isobutyl vinyl (IBVE) ethers with a well-characterized molecular structure. It is shown that ultrasonic treatment of disperse systems is of great importance for their stabilization. The results are highly dependent on the hydrophilic-hydrophobic polymers and their structure balance. The temperature dependence of polymethylvinyl ether solubility makes it possible to control polymer stabilizers surface activity.